2020
DOI: 10.3390/en13020337
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bipolar Conduction in Bandgap-Engineered n-Type Cu0.008Bi2(Te,Se)3 by Sulfur Doping

Abstract: Significant bipolar conduction of the carriers in Bi2Te3-based alloys occurs at high temperatures due to their narrow bandgaps. Therefore, at high temperatures, their Seebeck coefficients decrease, the bipolar thermal conductivities rapidly increase, and the thermoelectric figure of merit, zT, rapidly decreases. In this study, band modification of n-type Cu0.008Bi2(Te,Se)3 alloys by sulfur (S) doping, which could widen the bandgap, is investigated regarding carrier transport properties and bipolar thermal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A high ZT of ∼1.1 at 323 K was reported with the incorporation of Potassium and Tellurium in Bi 2 Te 3 [39]. Due to the reduction in bipolar conduction in Cu 0.008 Bi 2 (Se, Te) 3 with sulfur doping, a maximum ZT of ∼0.8 at 400 K was reported [40]. The multiscale architecture-engineered Cu 2-x S has been prepared by the wet chemical method.…”
Section: Introductionmentioning
confidence: 99%
“…A high ZT of ∼1.1 at 323 K was reported with the incorporation of Potassium and Tellurium in Bi 2 Te 3 [39]. Due to the reduction in bipolar conduction in Cu 0.008 Bi 2 (Se, Te) 3 with sulfur doping, a maximum ZT of ∼0.8 at 400 K was reported [40]. The multiscale architecture-engineered Cu 2-x S has been prepared by the wet chemical method.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports are published in reference to the zT enhancement in polycrystalline Bi 2 Te 3 by generating extrinsic point defects via doping foreign atoms. [19][20][21][22] Besides, introducing high order dimensional defects like grain boundaries and nanoinclusions, nanostructuring in the material also shows an impressive improvement in the thermoelectric performance due to low energy electron filtering and enhanced phonon scattering. 23,24 Tang et al reported an enhanced zT value of 1.4 at 400 K in p-type Zn x Bi 0.46 Sb 1.54 Te 3+x alloys, attributed to the mixed effect of defect complexity in nanostructuring.…”
Section: Introductionmentioning
confidence: 99%